Social Media Blueprints: A Study of Self-Representation and Identity Management - Mahmud, Malissa Maria; Wong, Shiau Foong (International Journal of Asian Social Science, 2021)
The landscape of social dimensions has tremendously changed with the existence of so-cial media as a powerful means to facilitate the process of creating and sharing infor-mation. The navigation, constructions and features of mediated communication fashion on social media have led to the forming of identity blueprints, consisting of narrative strategies in deploying and managing online identity. As a result, fascinating digital stories are formed wherein the content is curated to portray the desired identity. With the aim to examine the extent of gender-based perspective and tendencies in managing mediated identities through social media, this study employed a Mann-Whitney test to measure the variance between male and female responses. The results obtained indicate that statistically, there is a significant difference for both genders in the ways they manage their mediated selves and identities. This study also provides an insight on how social media platforms and specific interfaces like emojis are used as a tool to manage and shape mediated identity, reinforcing the concepts of online self-representation and identity management.